MISSILES AND AIRCRAFT (PART2) - Meyer, C.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
To understand the significance of air weapons and their effectiveness, you have to look at the situation at the close of the October Warand extrapolate ... TheSAMS were totally destroyed and the air force could do whatever it wanted against the ground.